2022
DOI: 10.21037/jgo-22-1134
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and validating of m7G-related genes prognostic signature for hepatocellular carcinoma and immune infiltration: potential biomarkers for predicting the overall survival

Abstract: Background: To investigate the prognostic significance of N7-methylguanosine (m7G) regulators and immune infiltration in liver hepatocellular carcinoma (LIHC).Methods: The research measured predictive m7G genes in LIHC samples from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) datasets. Data on the stemness index based on mRNA expression (mRNAsi), gene mutations, and corresponding clinical characteristics were obtained from TCGA and ICGC. Lasso regression was used to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It's also noteworthy that CST6 and DKK1 have been previously implicated in GC. For instance, CST6 is upregulated in the necroptosis-related genes prognostic index-high subgroup of STAD patients and is related to poor prognosis [28]. Similarly, DKK1 has been shown to correlate with poorer sur- vival rates in GC patients, through mechanisms that involve the creation of an immunosuppressive tumor microenvironment [29].…”
Section: Discussionmentioning
confidence: 99%
“…It's also noteworthy that CST6 and DKK1 have been previously implicated in GC. For instance, CST6 is upregulated in the necroptosis-related genes prognostic index-high subgroup of STAD patients and is related to poor prognosis [28]. Similarly, DKK1 has been shown to correlate with poorer sur- vival rates in GC patients, through mechanisms that involve the creation of an immunosuppressive tumor microenvironment [29].…”
Section: Discussionmentioning
confidence: 99%
“…The median was chosen to ensure a desirable statistical power to detect the difference of the two groups and to achieve robust groupings by eliminating the instability due to unevenly allocated sample sizes. Additionally, this rule has been commonly employed in the analysis of survival prognostic prediction with a multi-gene predictor [ 6 , 20 , 25 , 26 ].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Usually, a multi-gene predictor is more accurate than a single-gene predictor as the prognostic ability of a single gene is limited. A predictor optimally constructed from the selected genes becomes a useful biomarker for predicting survival in breast cancer [ 10 , 11 , 12 , 13 , 14 , 15 ], lung cancer [ 6 , 7 , 8 , 9 , 16 , 17 ], gastric cancer [ 18 , 19 ], ovarian cancer [ 20 , 21 , 22 , 23 , 24 ], skin cancer [ 25 ], liver cancer [ 26 , 27 ], bladder cancer [ 28 ], head and neck cancer [ 29 , 30 ], glioma [ 31 ], myeloproliferative neoplasms [ 32 ], kidney cancer [ 33 ], and cancers of mixed types [ 34 , 35 ]. These analyses were performed mostly based on univariate Cox regression with the significance scaling of p -values, such as 0.05, 0.01, and 0.001, followed by cross-validation and/or external validation.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have shown that m7G METTL1 or WDR4 is involved in regulating the occurrence and development of various cancers, such as liver cancer ( 15 ), head and neck squamous cell carcinoma ( 16 ), bladder cancer ( 17 ), colon cancer ( 18 ) and so on. In addition, m7G-related genes have been used to construct a prognostic model of the liver ( 19 ).…”
Section: Introductionmentioning
confidence: 99%